ANALISIS KEPUASAN KONSUMEN KOPI DI KEDAI-KEDAI KOPI DI KECAMATAN SAMIGALUH KABUPATEN KULON PROGO - Engri Sulistiawati; Danang Manumono (JURNAL ILMIAH AGRITAS, 2018)
This research was conducted in Samigaluh District, Kulon Progo Regency. Samigaluh has a unique local coffee, â€œmokaâ€ coffee, this coffee is made by farmers that is coffee plants side by side with cocoa plants to produce moka coffee. The goal of the research is to know the effect of product quality, service quality, age, work and income on the satisfaction of consumers of coffee in coffee shops in Samigaluh. The hypothesis of this study is predictable that product quality, service quality, age, occupation, and income affect the satisfaction of coffee consumers in coffee shops in Samigaluh District. The basic method used is descriptive method. The sampling method uses Accidental Sampling and Purposive Sampling with 50 respondents in totals. The analytical method uses multiple linear analysis, testing the coefficient of determination, F test, and partial t test. The results of the analysis of this study variables that have a significant effect on consumer satisfaction (Î± = 0,05) is product quality with a probability, service quality, age of respondent, and work of respondent. While the income variable is not significant to consumer satisfaction (p = 0.5521).